Pengaruh Current Ratio (CR), Return On Asset (ROA) dan Net Profit Margin (NPM) Terhadap Nilai Perusahaan Sub Sektor Tekstil dan Garment yang Terdaftar di Bursa Efek Indonesia periode 2018-2021 - Putri Sholeha Intan Permatasari; Teguh Purwanto (INDO PUBLISHING, 2026)
This study aims to determine the effect of CR, ROA and NPM on the value of companies in the textile and garment sub-sector which are listed on the Indonesia Stock Exchange for the 2018-2021 period. The population of this study is the textile and garment sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. Determination of the sample using purposive sampling technique so that there are 8 companies that meet the criteria as a research sample. This study uses quantitative methods and data sources using secondary data. Data collection techniques with documentation and data analysis techniques using classical assumption tests, multiple linear regression tests, the coefficient of determination and hypothesis testing using the t test and F test. The statistical test results show that ROA has a significant effect on firm value while CR and NPM have no effect on company value. company. Simultaneously CR, ROA and NPM have a significant effect on firm value.